2020
DOI: 10.1093/mnras/staa589
|View full text |Cite
|
Sign up to set email alerts
|

The Pristine survey XI: the FORS2 sample

Abstract: Extremely metal-poor (EMP) stars are old objects that mostly formed very early after the big bang. They are rare and, to select them, we have to rely on low-resolution spectroscopic or photometric surveys; specifically the combination of narrow- and broad-band photometry provides a powerful and time efficient way to select MP stars. The Pristine photometric survey is using the Canada–France–Hawaii Telescope MegaCam wide-field imager to obtain narrow-band photometry by utilizing a filter centred at 395.2 nm on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 78 publications
3
31
0
Order By: Relevance
“…The TOPoS sample provides an analysis of the same stars based on higher resolution spectra obtained by our group. We have a total of 70 stars (we excluded stars with upper limits in the high-resolution analysis, as well as stars for which MyGIsFOS did not converge), and they are summarised in Caffau et al (2018), with resolving power R ∼ 5000 and high S/N (typically above 100, 30 stars in common), and by Caffau et al (2020), with FORS at VLT, a resolving power of R ∼ 2000, and a high S/N (again above 100, three stars in common). In the Caffau et al (2018) sample, one star is analysed independently using two spectra.…”
Section: Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…The TOPoS sample provides an analysis of the same stars based on higher resolution spectra obtained by our group. We have a total of 70 stars (we excluded stars with upper limits in the high-resolution analysis, as well as stars for which MyGIsFOS did not converge), and they are summarised in Caffau et al (2018), with resolving power R ∼ 5000 and high S/N (typically above 100, 30 stars in common), and by Caffau et al (2020), with FORS at VLT, a resolving power of R ∼ 2000, and a high S/N (again above 100, three stars in common). In the Caffau et al (2018) sample, one star is analysed independently using two spectra.…”
Section: Accuracymentioning
confidence: 99%
“…The green dots are data fromCaffau et al (2018), and open symbols are stars with uncertain abundance according toCaffau et al (2018). The blue dots are data fromCaffau et al (2020). The stars circled in black are removed from the average (see text).…”
mentioning
confidence: 99%
“…We computed a synthetic spectrum with SYNTHE (see Kurucz 2005;Sbordone et al 2004) and the radial velocities were derived by templatematching (see e.g. Caffau et al 2020). Using the star's coordinates, radial velocities, Gaia Dr2 distances, and proper motions we characterised the stellar orbital parameters.…”
Section: Radial Velocity and Kinematicsmentioning
confidence: 99%
“…and for the 70 stars for which we have A(Ca) determination from Ca i lines [Ca/Fe] = +0.31 ± 0.10. To make this statement stronger, we compared our sample to the FORS-Pristine sample (Caffau et al 2020), which is a sample of similar metallicity stars, observed with the same spectrograph. These stars (open blue squares in the figure) generally show a larger scatter in [Mg/Fe] and [Ca/Fe], overall showing several stars with no evidence for the typical α-enhancement expected for the Galactic metal-poor stars.…”
Section: Abundancesmentioning
confidence: 99%
See 1 more Smart Citation